The modelling and simulation on burger production process: a case study in small and medium industry - Syarafun Nisa Zahelem (Institute of Engineering Mathematics, 2015)
The goal of the study is to find way to increase the production capacity and to observe the production process whenever the current resources and facilities are used with the increased production rate to achieve the goal of the study, the following objectives are identified; to study the characteristic of current burger production system; to construct a simulation model based on the existing burger production system; to apply the simulation model to find ways to increase the production capacity and enhance the production rate.